A novel secure blockchain framework for accessing electronic health records using multiple certificate authority - Ali, Aitizaz; Rahim, Hasliza A.; Ali, Jehad; Pasha, Muhammad Fermi; Masud, Mehedi; Rehman, Ateeq Ur; Chen, Can; Baz, Mohammed (Applied Sciences (Switzerland), 2021)
Blockchain is a promising technology in the context of digital healthcare systems, but there are issues related to the control of accessing the electronic health records. In this paper, we propose a novel framework based on blockchain and multiple certificate authority that implement smart contracts and access health records securely. Our proposed solution provides the facilities of flexible policies to update a record or invoke the policy such that a patient has complete authority. A novel approach towards multiple certificate’s authority (CA) is introduced in the design through our proposed framework. Our proposed policies and methods overcome the shortcoming and security breaches faced by single certificate authority. Our proposed scheme provides a flexible access control mechanism for securing electronic health records as compared to the existing benchmark models. Moreover, our proposed method provides a re-enrolment facility in the case of a user lost enrolment.
Keywords: Access control; Blockchain; Certificate authority; Efficiency; Security; Smart contracts